Cancer Cell Signaling 2014
DOI: 10.1201/b17138-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of PI3K in Combination with Dual HER2 Inhibitors is Required for Optimal Antitumor Activity in HER2+ Breast Cancer Cells

Abstract: Introduction: Despite multiple advances in the treatment of HER2+ breast cancers, resistance develops even to combinations of HER2 targeting agents. Inhibition of PI3K pathway signaling is critical for the efficacy of HER2 inhibitors. Activating mutations in PIK3CA can overlap with HER2 amplification and have been shown to confer resistance to HER2 inhibitors in preclinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…PIK3CA gene mutations acquired during disease progression are likely to relect increased activation of the PI3K pathway and therefore suggest possible implications in resistance [47]. Consistently with this hypothesis, in vitro data show that ErbB2 gene ampliication and PI3KCA gene mutations are associated with resistance to ErbB2-targeted agents [49,62,63] and PTEN loss or PIK3CA gene mutations have been linked to resistance to ErbB2 targeted therapy [48]. Since the serine/threonine kinase mTOR represents the inal sensor of the ErbB2-dependent activation of the PI3K/AKT pathway and it is negatively regulated by PTEN, it is conceivable that targeting mTOR might be more eicacious than targeting multiple pathways with diferent strategies [48,64] to interfere with tumor progression and to prevent resistance to ErbB2-targeted therapy.…”
Section: Overcoming Resistance To Targeted Therapysupporting
confidence: 69%
“…PIK3CA gene mutations acquired during disease progression are likely to relect increased activation of the PI3K pathway and therefore suggest possible implications in resistance [47]. Consistently with this hypothesis, in vitro data show that ErbB2 gene ampliication and PI3KCA gene mutations are associated with resistance to ErbB2-targeted agents [49,62,63] and PTEN loss or PIK3CA gene mutations have been linked to resistance to ErbB2 targeted therapy [48]. Since the serine/threonine kinase mTOR represents the inal sensor of the ErbB2-dependent activation of the PI3K/AKT pathway and it is negatively regulated by PTEN, it is conceivable that targeting mTOR might be more eicacious than targeting multiple pathways with diferent strategies [48,64] to interfere with tumor progression and to prevent resistance to ErbB2-targeted therapy.…”
Section: Overcoming Resistance To Targeted Therapysupporting
confidence: 69%
“…[4,5] Over-expression of HER-2/neu gene and it's protein are associated breast cancer patient's prognosis and therapy. [4] Trastuzumab (HerceptinÂź), a recombinant, humanized, monoclonal antibody targeting HER2 is well established as an effective treatment for HER2-positive breast cancer [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Rexer and group elegantly showed that acquisition of a hotspot PIK3CA mutation (either in helical or in kinase domain) is a mechanism of acquired resistance to lapatinib and that PIK3CA mutations partially uncouple PI3K from HER2 to permit the development and maintenance of resistance. Moreover, targeting of PI3K itself, in combination with maximal HER2 blockade with both an antibody and a TKI, is more effective than HER2 targeting alone for HER2+ breast tumors without PIK3CA mutations and this combination is definitely required for HER2+ breast tumors with PIK3CA mutations [85].…”
Section: Activation Of Pten-pi3k-akt-mtor Pathway and Anti-her2 Theramentioning
confidence: 98%